(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
Demonetization brought in an enormous spike in digital payments. Some government programs, such as Digital India, and the growing usage of various technologies, such as the Internet, are a method to encourage the rise in the use of digital payment. These changes improved transaction transparency for digital payments, strengthening the nation’s economy. Many developments have recently occurred in the payment system, such as digital wallets, UPI, and BHIM apps for easier execution of digital transactions. The current investigation looks into UPI in relation to the client’s chosen payment banks. It also demonstrates how banks are making it easy to increase their customer base. The goal of this article is to investigate the level of customer awareness and perception of UPI in India. The study additionally goes on to investigate the level of preparation, adoption, and customer satisfaction with the unified payment interface. Payment gateways have been identified as the most powerful engine driving the expansion of cashless and electronic payments. Payment gateways are rapidly expanding in India as a result of the proliferation of smart phones and 3G and 4G internet connectivity. The current study’s objective is to learn about people’s attitudes toward UPI and how they use it.